Scotland's Diaspora Strategy: The View from the Current American Diaspora. Issue 2 (May 2016) - Leith, Murray Stewart; Sim, Duncan
Abstract : Since devolution in 1999 and the establishment of a Scottish Government able to engage directly with the Scottish diaspora, a distinct diaspora strategy has been developed. It has tended to have an overly economic focus, in contrast with other countries like Ireland, which have adopted a more flexible approach, embracing cultural and heritage groups within the 'ancestral diaspora'. Research within Scottish diaspora organisations suggests that Scotland would benefit from a strategy which acknowledged in a more direct way the contribution which heritage groups can make to the homeland, for example through conservation projects, ancestral tourism or simply by being ambassadors for the country. It would also benefit from being less centrally managed, thereby giving diaspora organisations a more participative role.